The Dynamics and Implications of Recent Increases in Citrus Production Costs - Ronald P. Muraro; Robert A. Morris (EDIS)
FE793, a 9-page illustrated article by Ronald P. Muraro and Robert A. Morris, examines the magnitude of recent changes in citrus production costs for Florida growers and discusses their implications. Includes references. Published by the UF Department of Food and Resource Economics, March 2009.